2013
DOI: 10.1093/europace/eut237
|View full text |Cite
|
Sign up to set email alerts
|

The use of an integrated electroanatomic mapping system and intracardiac echocardiography to reduce radiation exposure in children and young adults undergoing ablation of supraventricular tachycardia

Abstract: Use of an integrated EAM/ICE system was no better than EAM alone in limiting radiation, but can be helpful for transseptal punctures. Given the low dose savings, use of ICE may be weighed against its financial cost. Low-fluoroscopy cases are performed in most NFI procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 14 publications
(7 reference statements)
2
69
0
1
Order By: Relevance
“…Six studies reported zero (0) peri‐procedural complications in one or both arms 10,26–28,30,36 and there was no observable heterogeneity among the 13 studies included in the analysis (I 2 = 0%) 11,22,24,26–28,30–32,34,36–38 . A nonsignificant decrease in complications was demonstrated in ablations with the use of ICE vs no ICE (RR 0.66; 95% CI, 0.42‐1.05, P = .08) (Figure S3C).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Six studies reported zero (0) peri‐procedural complications in one or both arms 10,26–28,30,36 and there was no observable heterogeneity among the 13 studies included in the analysis (I 2 = 0%) 11,22,24,26–28,30–32,34,36–38 . A nonsignificant decrease in complications was demonstrated in ablations with the use of ICE vs no ICE (RR 0.66; 95% CI, 0.42‐1.05, P = .08) (Figure S3C).…”
Section: Resultsmentioning
confidence: 96%
“…Nineteen studies with a total sample size of 2186 patients were included in the main analysis, encompassing patients with any form of atrial or ventricular arrhythmia undergoing catheter ablation (see Table S2 for individual study details) 10,22–38 . The characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, in this setting, left sided accessory pathways requiring transeptal puncture were not studied. As discussed subsequently in the section on, atrial fibrillation ablation, intracardiac echography (ICE) may eventually play a role in reducing fluoroscopy exposure during transeptal puncture 38 , but such an approach still needs to be standardized and validated.…”
Section: Atrioventricular Re-entrant Tachycardia Reciprocating Atriomentioning
confidence: 99%
“…The most successful strategy for reducing the risk of ionizing radiation for all parties involved would be to minimize exposure altogether (both time and dose). Ancillary imaging modalities (such as 3DM and ultrasound) that do not utilize ionizing radiation are important and often underused tools that may reduce reliance on radiation‐based imaging modalities . When coupled with other dose reduction strategies (including reduced frame rate, adjusting tube voltage and tube current, and use of collimation) exposure to ionizing radiation can be drastically reduced .…”
Section: Discussionmentioning
confidence: 99%